SEM analysis of kenaf sandwich panel - Halim, Zahurin; Othman, Maizatulnisa; Abdul Rahman, Siti Khadijah (Trans Tech Publications, Switzerland, 2015)
This study focus on the cross-sectional image of sandwich panel; the kenaf dispersion in core and the skin core interaction. Fracture image is the image outcome of flexural test. The main element of the core structure is kenaf and the skin used in this study is galvanised steel sheet. Skin thickness being used in this research is 1.0 mm and 1.2 mm.